1998
DOI: 10.1677/joe.0.157r001
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous induction of fetal membrane prostaglandin production precedes clinical labour

Abstract: Fetal membranes from term human pregnancies produce prostaglandins, and may respond to bacterial endotoxin or interleukin-1ß (IL-1ß) with increased prostaglandin E2 (PGE2) production. The effects of endotoxin persisted for up to 24 h, whereas those of IL-1ß were maximal 4-8 h after addition. The maximum levels of PGE2 (200-350 pg/ml) were similar in all experiments, and were independent of the stimulus used. Not all tissues responded to these stimuli; those which did not had basal levels of PGE2 production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
4
46
0
Order By: Relevance
“…Serum PGE 2 levels, which peaked during onset of labor, were reduced significantly after parturition. This is in accord with earlier studies demonstrating that the serum PGE 2 level increases at onset of labor (7,18). The results of different studies should be interpreted considering the characteristics of the study population, the methods of sample collection, the clinical status of patients at the time of sample collection, the time point at which the samples were collected, and the method used for estimation of PGE 2.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Serum PGE 2 levels, which peaked during onset of labor, were reduced significantly after parturition. This is in accord with earlier studies demonstrating that the serum PGE 2 level increases at onset of labor (7,18). The results of different studies should be interpreted considering the characteristics of the study population, the methods of sample collection, the clinical status of patients at the time of sample collection, the time point at which the samples were collected, and the method used for estimation of PGE 2.…”
Section: Discussionsupporting
confidence: 84%
“…High levels of cycloxygenase-2 are expressed in fetal membranes prior to labor (7). After parturition, involution of various intrauterine tissues occurs, thus restoring the serum PGE 2 level to normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of PTB are multiple, but intra-amniotic infection and chorioamnionitis are thought to be a major cause of spontaneous preterm labor (PTL) and preterm premature rupture of the fetal membranes (PPROM). Extensive data from the literature have reported mechanisms involving a feed-forward loop network in normal parturition, where proinflammatory cytokines are able to stimulate production of PGs and thereby uterine contractions and to upregulate matrix metalloproteinase (MMP) activation and programmed cell death (apoptosis), leading to the weakening and the rupture of the fetal membranes (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Disks of intact tissue were cut using a sharpened punch and cultured in Medium 199 supplemented with ITS (insulin, transferrin, selenium and linoleic acid, all at 0·63 mg/ml, and BSA at 0·13 mg/ml; Sigma) in multiwell tissue culture plates for 24 h at 37 C in an atmosphere of 5% CO 2 /95% air. The medium was also supplemented with 1 mM aspirin, as we have shown that fetal membranes may be preactivated and spontaneously release high levels of PGE 2 (Brown et al 1998). After this time the medium was changed, the tissue washed with medium containing no aspirin, and incubated with or without IL-1 , IL-1 or IL-1ra or combinations of these for time periods stated in the Results section.…”
Section: Tissue Collection and Culturementioning
confidence: 99%